Not only a small liver - The pathologist’s perspective in the pediatric liver transplant setting - Gambella, Alessandro; Mastracci, Luca; Caporalini, Chiara; Francalanci, Paola; Mescoli, Claudia; Ferro, Jacopo; Alaggio, Rita; Grillo, Federica (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2022)
Pediatric liver transplantation represents a safe and long-lasting treatment option for various disease types, requiring the pathologist’s input. Indeed, an accurate and timely diagnosis is crucial in reporting and grading native liver diseases, evaluating donor liver eligibility and identifying signs of organ injury in the post-transplant follow-up. However, as the procedure is more frequently and widely performed, deceptive and unexplored histopathologic features have emerged with relevant consequences on patient management, particularly when dealing with long-term treatment and weaning of immunosuppression. In this complex and challenging scenario, this review aims to depict the most relevant histopathologic conditions which could be encountered in pediatric liver transplantation. We will tackle the conditions representing the main indications for transplantation in childhood as well as the complications burdening the post-transplant phases, either immunologically (i.e., rejection) or non-immunologically mediated. Lastly, we hope to provide concise, yet significant, suggestions related to innovative pathology techniques in pediatric liver transplantation.